The Dynamic of Social Changes of Muslim Community Toward Water Park Tourism in Maguwoharjo Tourism Village, Sleman, Yogyakarta - Tutuk Ningsih (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2019)
Society consists of several persons who live together to create culture. Thus without the existence of a society as a place for cultural growth, culture will not exist. Jogja Bay Waterpark Tourism is considered to be one of the biggest water park tourism in Southeast Asia which attracts many local and foreign tourists. The purpose of this study is finding out the dynamics of social change in society, especially Muslim communities around tourism area. Data retrieval is done by interviewing some people and clergy leaders around the Jogja Bay Waterpark. The results of this study find that there is an impact of positive changes in the economic sector, whereas in the socio-cultural field, there is a significant impact on the behavioral pattern of Muslim communities towards the negative, especially the youth caused by the existence of foreign cultures.